2009
DOI: 10.1016/j.yqres.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary vegetation dynamics in a biodiversity hotspot, the Uluguru Mountains of Tanzania

Abstract: Late Quaternary vegetation history and environmental changes in a biodiverse tropical ecosystem are inferred from pollen, charcoal and carbon isotope evidence derived from a ∼ 48,000-yr sedimentary record from the Uluguru Mountains, a component of the Eastern Arc Mountains of Kenya and Tanzania. Results indicate that Eastern Arc forest composition has remained relatively stable during the past ∼ 48,000 yr. Long-term environmental stability of the Eastern Arc forests has been proposed as a mechanism for the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 69 publications
8
50
0
Order By: Relevance
“…Instead, an important dampening effect of the IOD on long-term climate change was suggested. Stable temperatures across the LGM, and during the Last Glacial to Holocene transition, are known from the Tanzanian Eastern Arc Mountains (Mumbi et al, 2008;Finch et al, 2009). These studies suggested that moist Indian Ocean air masses caused long-term ecosystem stability.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, an important dampening effect of the IOD on long-term climate change was suggested. Stable temperatures across the LGM, and during the Last Glacial to Holocene transition, are known from the Tanzanian Eastern Arc Mountains (Mumbi et al, 2008;Finch et al, 2009). These studies suggested that moist Indian Ocean air masses caused long-term ecosystem stability.…”
Section: Introductionmentioning
confidence: 99%
“…This difference could result from locally drier conditions that characterize the northern slope as compared to the humid southern slope, and which most likely result in a different vegetation response to climate change. Furthermore, southward in the Eastern Arc Mountains, stable forest distribution and composition is observed through the LGM which seems to be explained by continuous humid conditions maintained by the Indian Ocean influence (Finch, Leng, & Marchant, ; Mumbi, Marchant, Hooghiemstra, & Wooller, ). On Mt.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these records reveal a picture of cooling climate in eastern Africa at the time when Magubike was first occupied, a p p r o x i m a t e l y 6 5 , 0 0 0 B P. M o r e s p e c i f i c paleoenvironmental data for the Iringa region is unfortunately limited. Lake cores from the Eastern Arc Mountains,~40 km to the east of Magubike, show long-term climate stability dating back to at least~48,000 BP, but do not necessarily imply climate stability further back in time (Finch et al 2009;Mumbi et al 2008). Environmental analysis of Magubike and its surrounding topography is planned for the near future to extend this sequence further back into the MSA and to test the environmental hypotheses explored in this article.…”
Section: Palaeoclimate Of Eastern Africamentioning
confidence: 99%